Effect of CO₂ and Argon Gas Shielding on GMAW Welding Joint Quality - Safira Ma'asya; Muhammad Alfharizi; Togu Julianman Manullang; Andrean Bastian Tawaris; Fardin Hasibuan; Muhammad Irsyam (METALOGRAM, 2026)
This study aims to evaluate the effect of shielding gas types, namely carbon dioxide (CO₂) and argon, on the quality of welded joints in the Gas Metal Arc Welding (GMAW) process with low carbon steel as the base material. The research method was carried out experimentally using a steel plate measuring 150 mm × 75 mm × 6 mm and an ER70S-6 electrode wire with a diameter of 1.0 mm. The welding process was carried out with an inverter-type GMAW machine using fixed parameters: 120 ampere current, 22 volt voltage, 4 mm/s welding speed, 12 mm stick-out distance, and 15 liters per minute shielding gas flow rate. The specimens were divided into two groups based on the shielding gas, namely pure CO₂ and pure argon. Evaluation of the joint quality was carried out through tensile tests, Vickers hardness tests on three main zones (weld metal, heat affected zone, and base metal), as well as microstructure and visual observations. The results showed that the specimens with argon gas had a higher average tensile strength (460 MPa) than CO₂ (420 MPa). The hardness values were also higher and more even in the argon specimens, with a finer and more uniform microstructure. In conclusion, the use of argon produces welds with better mechanical and metallurgical qualities than CO₂. Therefore, argon is more recommended for welding low carbon steels that require high strength and precision.